Showa, 1939-1944 : a history of Japan - Mizuki, Shigeru, 1922-2015 (Drawn & Quarterly, 2014)
Continues Mizuki's autobiographical and historical account of Showa-era Japan. This volume covers the final moments of the lead-up to World War II and the first few years of the Pacific War, and is a chilling reminder of the harshness of life in Japan during this highly militarized epoch.